PENGUKURAN KINERJA UNIT KERJA PEMERINTAH DAERAH DALAM PERSPEKTIF VALUE FOR MONEY - Hidayat, Taufik Wahyu; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze the performance assessment at DinasPendidikan Kota Surabaya which is measured by using value for money perspective. The researchmethod has been conducted by using qualitative descriptive and the source of data is the primary andthe secondary data. The result of the analysis and the discussion about the performance assessment oflocal government work unit in the value for money perspective at Dinas Pendidikan Kota Surabaya in2013 and 2014, shows that in determining the performance of the economy considers the budget(input) and the realization of the budget, efficient performance can be seen from the number of therealization of the output which has been generated to the input, effective performance can be seen fromrealization of the output in running the objective of the agency that achieving the expected program.The development of relevant peformance assessment model is required to obtained the result of reliabledata so the result of measurement will consistent from time to time if the meaured phenomena remainsthe same.Keywords: Value for Money, Economy, Efficient, Effectiveness